Preface and Interviews - J. Mokhoathi; L. Sutton (Acta Theologica)
During 2020-2021 the Faculty of Theology and Religion at the University of the Free State celebrated its 40 years of existence, using the theme “Transforming theology and religion?”. Part of the celebration is this publication, which is dedicated to the Faculty of Theology and Religion and all of her staff through the first 40 years. As part of the celebration, we asked Prof. Francois Tolmie, a former student, dean and current professor in the Faculty, to provide us with a reflection of his own experiences in the Faculty over the past 40 years, whereafter we asked the current Dean, Prof. Rantoa Letšosa a few question on how he perceives the future of the Faculty.